An imidazolium-based supramolecular gelator enhancing interlayer adhesion in 3D printed dual network hydrogels. (August 2021) - Zhou, Zuoxin; Samperi, Mario; Santu, Lea; Dizon, Glenieliz; Aboarkaba, Shereen; Limón, David; Tuck, Christopher; Pérez-García, Lluïsa; Irvine, Derek J.; Amabilino, David B.; Wildman, Ricky
Graphical abstract: Highlights: An LMWG compound formed a supramolecular network during extrusion-based 3D printing providing structural support to the monomer. The monomer in all printed layers is cured simultaneously during post-processing. Excellent inter- and intra-layered isotropy was achieved in double-network hydrogels. The tensile properties were close to those fabricated using mould casting. The gelator fibrillar network was embedded and physically interpenetrated in the polymer structure. Abstract: The variety of UV-curable monomers for 3D printing is limited by a requirement for rapid curing after each sweep depositing a layer. This study proposes to trigger supramolecular self-assembly during the process by a gemini imidazolium-based low-molecular-weight gelator, allowing printing of certain monomers. The as-printed hydrogel structures were supported by a gelator network immobilising monomer:water solutions. A thixotropic hydrogel was formed with a recovery time of <50 s, storage modulus = 8.1 kPa and yield stress = 18 Pa, processable using material extrusion 3D printing. Material extrusion 3D printed objects are usually highly anisotropic, but in this case the gelator network improved the isotropy by subverting the usual layer-by-layer curing strategy. The monomer in all printed layers was cured simultaneously during post-processing to form a continuous polymeric network. The two networks then physically interpenetrate to enhance mechanical performance. The double network hydrogels fabricated with layers cured simultaneously showed 62–147% increases in tensile properties compared to layer-by-layer cured hydrogels. The results demonstrated excellent inter- and intra-layered coalescence. Consequently, the tensile properties of 3D printed hydrogels were close to mould cast objects. This study has demonstrated the benefits of using gelators to expand the variety of 3D printable monomers and shown improved isotropy to offer excellent mechanical performances.